Interactive rendering of translucent materials under area lights using voxels and Poisson disk samples - Koa, Ming Di (2020)
Interactive rendering of translucent materials in virtual worlds has always proved to be challenging. Rendering their indirect illumination produces further challenges. In our work, we develop a voxel illumination framework for translucent materials illuminated by area lights. Our voxel illumination uses two existing voxel structures, the Enhanced Subsurface Light Propagation Volumes (ESLPV), which handles the local translucent material appearance and the Light Propagation Volumes (LPV), which handles indirect illumination for the surrounding diffuse surfaces. By using a set of sparse translucent Poisson disk samples (TPDS) and diffuse Poisson disk samples (DPDS) for the ESLPV and LPV, illumination can be gathered from area lights effectively. This allows the direct illumination of the translucent material to be rendered in the ESLPV, and the diffuse indirect illumination of the surrounding scene can be rendered in the LPV. Based on experiments, a small number of Poisson disk samples in each voxel are sufficient to produce good results. A uniform set of Poisson disk samples on the translucent objects is resampled and chosen as Translucent Planar Lights (TPLs) and is used to distribute lighting from translucent objects into the LPV by an additional gathering process. Our technique allows for direct and indirect illuminations from highly scattering translucent materials to be rendered interactively under area lighting at good quality. We can achieve similar effects, such as low-frequency scattered light illumination from translucent materials, when compared to offline renderers without precomputations.